Carbide supported cobalt catalyst and preparation method and application thereof

By using CaCl2 or MgCl2 as flux, the Co catalyst is immobilized on the MXene support, the stability and leaching problems of transition metal catalysts in the prior art are solved, and efficient organic pollutant degradation and catalyst stability are achieved.

CN119771458AActive Publication Date: 2025-04-08ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202510117129.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-08
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

In the prior art, when dealing with difficult-to-degrade organic pollutants, the stability and leaching problems of transition metal catalysts are more prominent, and there are problems of oxidation and catalyst leaching during the etching of MAX.

Method used

MXene is obtained by thermal decomposition of molten salt by using CaCl2 or MgCl2 as molten salt etchant, and the Co catalyst is fixed on the MXene support using a mixture of cobalt source and chloride salt to form a carbide-supported cobalt catalyst.

Benefits of technology

The stability of the catalyst and the ability to activate PMS are improved, the leaching of Co is reduced, the catalytic performance is significantly improved, and the specific surface area and loading site are increased through the unique flower-like structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771458A_ABST
    Figure CN119771458A_ABST
Patent Text Reader

Abstract

The invention provides a carbide-loaded cobalt catalyst as well as a preparation method and application thereof. The obtained carbide-loaded cobalt catalyst has high catalytic activity. According to the method, MAX is taken as a raw material, and a cobalt catalyst is anchored on an MXene carrier in the process of etching the molten salt to obtain the MXene. The carbide-loaded cobalt catalyst has a special flower-shaped or accordion-shaped structure, so that the carbide-loaded cobalt catalyst has a relatively large specific surface area and more catalyst loading sites, and is beneficial to activation of PMS by cobalt and degradation of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental purification materials, and specifically relates to a carbide-supported cobalt catalyst and a preparation method and application thereof. Background Art

[0002] Based on hydroxyl radicals (OH·) and sulfate radicals (SO4 ·- Advanced oxidation processes (AOPs) are currently considered to be an effective method for treating refractory organic pollutants. Common transition metals, such as Ni, Fe, Co and their compounds, are excellent activators of peroxymonosulfate (PMS).

[0003] MXene is a general term for a large class of new two-dimensional transition metal nitrides / carbides. MXene is usually obtained by selectively etching the "A"-site element in MAX. The preparation methods of MXene can be divided into two types: fluorine-containing etching and fluorine-free etching. Compared with the more dangerous hydrofluoric acid etching method, the anions obtained by thermal decomposition of Lewis acid salts at high temperature react with type A atoms to remove them. This etching method is safe and gentle, and the end groups on the MXene surface are controllable, making it more suitable for loading single atoms. The active cations in the molten salt oxidize the A-site element (such as Al) to form a new molten salt, and the metal cations are reduced to a metallic state and anchored on the MXene surface. The molten salts that can be used as etchants in current reports have evolved from chloride salts represented by ZnCl2, CoCl2, and CuCl2 to other halide molten salts such as CuBr2 and CuI2, as well as their binary or ternary mixtures. In order to promote the etching of A, alkali metal chlorides such as NaCl and KCl can also be used as fluxes. Currently, CaCl 2、 There are few studies on alkaline earth metal chlorides such as MgCl2 as fluxes, especially the one-step molten salt etching of molybdenum-based MAX and the simultaneous preparation of carbide-loaded cobalt catalysts. Summary of the invention

[0004] The object of the present invention is to provide a carbide-supported cobalt catalyst and a preparation method and application thereof, wherein the catalyst has the characteristics of high catalytic activity. The present invention uses MAX as a raw material and CaCl2 or MgCl2 as a molten salt etchant, and can realize functionalization in the process of obtaining MXene by thermal decomposition of molten salt. The bimetallic chloride salt not only removes the A-type atoms, but also fixes Co on the MXene carrier at the same time. The obtained catalyst selects CaCl2 or MgCl2 as an etchant, giving full play to the advantages of metal chlorides. The addition of CaCl2 or MgCl2 is conducive to the dispersion of Co, so that Co is more stably fixed on MXene, which enhances the activation of PMS and reduces the leaching of Co. The catalyst uses the highly stable MXene as a catalytic platform, uses single-atom sites to activate PMS, has excellent catalytic performance, and can effectively purify pollutants in wastewater.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] In a first aspect, the present invention provides a carbide-supported cobalt catalyst, wherein the carbide-supported cobalt catalyst is prepared by the following method:

[0007] (1) grinding the MAX phase in an agate mortar; the MAX phase is one or two of Mo2TiAlC2 and Mo3AlC2 (preferably Mo2TiAlC2);

[0008] (2) Adding a cobalt source and a chloride salt to the ground MAX phase fine powder of step (1), grinding the mixture thoroughly to obtain a mixed powder; wherein the ratio of the MAX phase to the cobalt source and the chloride salt is 0.5 mmol: 0.0125-0.25 mmol: 0.25-1 mmol (preferably 0.5 mmol: 0.125 mmol: 0.5 mmol).

[0009] (3) transferring the mixed powder in step (2) into a covered alumina crucible, placing it into a tube furnace, calcining it at 750-800° C. for 4-6 h (preferably at 750° C. and for 6 h) under nitrogen protection, and cooling it naturally in the tube furnace to obtain a calcined carbide-supported cobalt catalyst;

[0010] (4) Pour the carbide-supported cobalt catalyst obtained by calcining step (3) into an appropriate amount of deionized water, disperse it evenly by ultrasonication, wash it by centrifugation several times, and dry it at 40-80° C. for 12-24 h (preferably the drying temperature is 60° C. and the preferred drying time is 24 h) to obtain a catalyst.

[0011] Furthermore, the cobalt source in step (2) is an inorganic cobalt salt CoCl2·6H2O.

[0012] Furthermore, the chloride salt in step (2) is one or more of CaCl2 and MgCl2·6H2O mixed in any proportion.

[0013] Furthermore, the heating rate in step (3) is 2-5°C / min (preferably 5°C / min).

[0014] On the other hand, the present invention provides a use of a carbide-supported cobalt catalyst in activating persulfate (PMS) to degrade organic pollutants.

[0015] Furthermore, the organic pollutant is a mixture of one or more of fluorouracil, metronidazole, sulfamethoxazole, perfluorooctanoic acid, and norfloxacin. In one embodiment of the present invention, the organic pollutant used is fluorouracil.

[0016] Since the catalytic degradation function of the carbide-supported cobalt catalyst in the present invention is achieved by activating PMS, the present invention team can foresee that any organic pollutants that can be degraded by PMS are within the protection scope of the present invention.

[0017] The specific application method is: evenly disperse the carbide-loaded cobalt catalyst in the aqueous solution of organic pollutants, then add persulfate and stir to achieve the degradation process.

[0018] Furthermore, the concentration of organic pollutants in the aqueous solution of organic pollutants is 10-50 mg / L.

[0019] Furthermore, the persulfate is one or a mixture of peroxymonosulfate and peroxydisulfate; in one embodiment of the present invention, it is potassium hydrogen persulfate.

[0020] Furthermore, based on the volume of the aqueous solution of organic pollutants, the mass of the catalyst ranges from 0.5 to 1 g / L.

[0021] Furthermore, also based on the volume of the aqueous solution of organic pollutants, the mass range of the persulfate is 0.5-1 g / L.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. Molten salt as a reaction medium can provide a good environment for the formation of molybdenum carbide and the loading of Co catalyst, which can effectively reduce the oxidation of MAX and the leaching of Co catalyst during the etching process.

[0024] 2. In the mixture of cobalt source and chloride salt, with the assistance of chloride salt, the Co catalyst can be firmly anchored on the molybdenum carbide / titanium carrier.

[0025] 3. In addition to trying CaCl2 as a flux, the present invention also selected another alkaline earth metal chloride (MgCl2). A mixed molten salt etchant consisting of calcium chloride or magnesium chloride and a small amount of cobalt chloride can successfully etch the MAX phase and form a Co catalyst load through a one-step calcination.

[0026] 4. The main phase of the carbide-supported cobalt catalyst in the present invention is Mo2C, and the morphology is a three-dimensional flower-like structure. This unique flower-like structure enables it to have a larger specific surface area and more catalyst loading sites.

[0027] 5. The main phase of the carbide-supported cobalt catalyst in the present invention is Ti3C2, which is derived by etching the MAX phase through a high-temperature molten salt method (CoCl2 / CaCl2 mixed molten salt) and using the MXene phase as a substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The SEM images of the catalysts prepared in Example 2, Example 4 and Comparative Example 3 at different scales are shown in FIG. Ca-750 ), c is Example 4 (Mo-Co / 40 Mg-750 ), d is Comparative Example 3 (Ti-Co / 20 Ca-750 ).

[0029] Figure 2 The catalyst Mo-Co / 4 prepared in Example 2 Ca-750 , the catalyst Mo-Co / 40 prepared in Example 4 Mg-750 , the catalyst Ti-Co / 20 prepared in Comparative Example 3 Ca-750 XRD pattern of . DETAILED DESCRIPTION

[0030] Example 1

[0031] 0.5mmol Mo2TiAlC2, 0.25mmol CoCl2·6H2O, and 0.25mmol CaCl2 were put into an agate mortar and ground thoroughly. The mixed powder was transferred to a covered alumina crucible and placed in a tube furnace. Under nitrogen protection, the temperature was raised to 750℃ at 5℃ / min and kept at this temperature for 6h. After cooling to room temperature, deionized water was added and the washing was repeated 4 times. The sample was dried at 60℃ for 24h. The sample was recorded as Mo-Co / 2 Ca / 2-750 .

[0032] Example 2

[0033] Take 0.5mmol Mo2TiAlC2, 0.125mmol CoCl2·6H2O, and 0.5mmol CaCl2 and grind them thoroughly in an agate mortar. Transfer the mixed powder into a covered alumina crucible and put it into a tube furnace. Under nitrogen protection, set the heating gradient to 5℃ / min. -1 The reaction temperature was 750 °C, heated for 6 h, cooled to room temperature, added with deionized water, washed 4 times, and dried at 60 °C for 24 h. The catalyst sample was recorded as Mo-Co / 4 Ca-750 .

[0034] Example 3

[0035] Take 0.5mmol Mo2TiAlC2, 0.125mmol CoCl2·6H2O, and 1mmol CaCl2 and grind them thoroughly in an agate mortar. Transfer the mixed powder into a covered alumina crucible and put it into a tube furnace. Under nitrogen protection, set the heating gradient to 5℃ / min. -1 The reaction temperature was 750 °C, heated for 6 h, cooled to room temperature, added with deionized water, washed 4 times, and dried at 60 °C for 24 h. The catalyst sample was recorded as Mo-Co / 4 2Ca-750 .

[0036] Example 4

[0037] Take 0.5mmol Mo2TiAlC2, 0.0125mmol CoCl2·6H2O, and 0.5mmol MgCl2·6H2O and grind them thoroughly in an agate mortar. Transfer the mixed powder into a covered alumina crucible and put it into a tube furnace. Under nitrogen protection, set the heating gradient to 5℃ / min. -1 The reaction temperature was 750 °C, heated for 6 h, cooled to room temperature, added with deionized water, washed 4 times, and dried at 60 °C for 24 h. The catalyst sample was recorded as Mo-Co / 40 Mg-750 .

[0038] Example 5

[0039] Take 0.5mmol Mo2TiAlC2, 0.25mmol CoCl2·6H2O, and 0.25mmol CaCl2 and grind them thoroughly in an agate mortar. Transfer the mixed powder into a covered alumina crucible and put it into a tube furnace. Under nitrogen protection, set the heating gradient to 5℃ / min. -1 The reaction temperature was 550 °C, heated for 6 h, cooled to room temperature, added with deionized water, washed 4 times, and dried at 60 °C for 24 h. The catalyst sample was recorded as Mo-Co / 2 Ca / 2-550 .

[0040] Comparative Example 1

[0041] Take 0.5mmol Mo2TiAlC2, 0.25mmol CoCl2·6H2O, and 0.25mmol CaCl2 and grind them thoroughly in an agate mortar. Transfer the mixed powder into a covered alumina crucible and put it into a tube furnace. Under nitrogen protection, set the heating gradient to 5℃ / min. -1 The reaction temperature was 850 °C, heated for 6 h, cooled to room temperature, added with deionized water, washed 4 times, and dried at 60 °C for 24 h. The catalyst sample was recorded as Mo-Co / 2 Ca / 2-850 .

[0042] Comparative Example 2

[0043] Take 1mmol Ti3AlC2, 0.5mmol CoCl2·6H2O, and 0.5mmol CaCl2 and grind them thoroughly in an agate mortar. Transfer the mixed powder into a covered alumina crucible and put it into a tube furnace. Under nitrogen protection, set the heating gradient to 5℃ / min. -1 The reaction temperature was 750 °C, heated for 6 h, cooled to room temperature, added with deionized water, washed 4 times, and dried at 60 °C for 24 h. The catalyst sample was recorded as Ti-Co / 2 Ca / 2-750 .

[0044] Comparative Example 3

[0045] Take 1mmol Ti3AlC2, 0.05mmol CoCl2·6H2O, and 1mmol CaCl2 and grind them thoroughly in an agate mortar. Transfer the mixed powder into a covered alumina crucible and put it into a tube furnace. Under nitrogen protection, set the heating gradient to 5℃ / min. -1 The reaction temperature was 750 °C, heated for 6 h, cooled to room temperature, added with deionized water, washed 4 times, and dried at 60 °C for 24 h. The catalyst sample was recorded as Ti-Co / 20 Ca-750 .

[0046] Comparative Example 4

[0047] Take 1mmol Ti3AlC2, 0.025mmol CoCl2·6H2O, and 1mmol CaCl2 and grind them thoroughly in an agate mortar. Transfer the mixed powder into a covered alumina crucible and put it into a tube furnace. Under nitrogen protection, set the heating gradient to 5℃ / min. -1 The reaction temperature was 750 °C, heated for 6 h, cooled to room temperature, added with deionized water, washed 4 times, and dried at 60 °C for 24 h. The catalyst sample was recorded as Ti-Co / 40 Ca-750 .

[0048] Comparative Example 5

[0049] Take 0.5mmol Mo2TiAlC2, 0.125mmol cobalt phthalocyanine, and 0.5mmol CaCl2 and grind them thoroughly in an agate mortar. Transfer the mixed powder into a covered alumina crucible and put it into a tube furnace. Under nitrogen protection, set the heating gradient to 5℃ / min. -1 The reaction temperature was 750 °C, heated for 6 h, cooled to room temperature, added with deionized water, washed 4 times, and dried at 60 °C for 24 h. The catalyst sample was recorded as Mo-Co T / 4 Ca-750 .

[0050] Comparative Example 6

[0051] Take 0.5mmol Mo2TiAlC2, 0.0125mmol cobalt phthalocyanine, and 0.5mmol MgCl2·6H2O and grind them thoroughly in an agate mortar. Transfer the mixed powder into a covered alumina crucible and put it into a tube furnace. Set the heating gradient to 5℃ / min under nitrogen protection. -1 The reaction temperature was 750 °C, heated for 6 h, cooled to room temperature, added with deionized water, washed 4 times, and dried at 60 °C for 24 h. The catalyst sample was recorded as Mo-Co T / 40 Mg-750 .

[0052] Application comparison experiment

[0053] 1. Catalytic degradation test of organic matter: A 20 mg / L fluorouracil solution was prepared to simulate organic pollutants. 25 mg of the samples of the embodiment and the comparative example were respectively placed in 50 mL of the fluorouracil solution, and 25 mg of potassium persulfate (PMS) was added. A small amount of the solution was filtered 5 min, 10 min and 30 min after the reaction, and the absorbance of the residual fluorouracil in the solution after filtration was tested with an ultraviolet spectrophotometer. The degradation rate of the sample to fluorouracil was calculated, as shown in Table 1.

[0054] 2. Co ion leaching test: Take 5 mL of the filtered degradation reaction solution and test the Co ion leaching concentration. The results are shown in Table 1.

[0055] Table 1 Sample degradation rate data

[0056]

[0057]

[0058] 1. The degradation data of fluorouracil in Examples 1-5 show that the catalyst prepared in the present invention has excellent catalytic performance and an ideal Co ion leaching concentration. The catalytic performance is higher than 85%, and the Co ion leaching concentration is lower than 5.

[0059] 2. It can be seen from Example 1, Example 5 and Comparative Example 1 that the catalysts prepared at different temperatures have a high degradation efficiency. When the temperature is high (850°C) or low (550°C), the cobalt ion leaching level of the catalyst obtained under the corresponding conditions will increase, and the most suitable temperature is 750-800°C.

[0060] 3. Examples 1-3 show that by appropriately reducing the content of cobalt chloride and increasing the content of calcium chloride, the flower-shaped molybdenum carbide-based catalyst prepared by the present invention still maintains a relatively high catalytic activity and a relatively low level of cobalt ion leaching.

[0061] 4. It can be illustrated by Examples 2 and 4 that when MAX is Mo2TiAlC2, both calcium chloride and magnesium chloride can ensure that the catalyst prepared by the present invention can efficiently degrade fluorouracil.

[0062] 5. It can be shown from Example 1 and Comparative Example 2 that when calcium chloride is selected as the flux and the MAX phase is replaced by Ti3AlC2 from Mo2TiAlC2, the catalytic performance of the prepared catalyst is still high, but the leaching of cobalt ions will be significantly increased.

[0063] 6. It can be seen from Example 2 and Comparative Example 5 that the cobalt salts used in the present invention, CoCl2·6H2O and cobalt phthalocyanine, can both ensure the high catalytic activity of the catalyst prepared by the present invention, but CoCl2·6H2O will significantly reduce the level of cobalt ion leaching.

[0064] 7. Comparative Examples 2-4 show that when MAX is Ti3AlC2, calcium chloride can also be used as a flux to help the transition metal cobalt exert its catalytic activity and activate PMS to degrade fluorouracil, but there will be a high leaching concentration of cobalt ions or low catalytic performance.

[0065] 8. It can be shown from Example 4 and Comparative Example 6 that CoCl2·6H2O can effectively improve the catalytic performance of the catalyst compared with cobalt phthalocyanine.

[0066] Figure 1 The SEM images of the catalysts prepared in Example 2, Example 4 and Comparative Example 3 are of different scales. Ca-750 , c is Mo-Co / 40 Mg-750 , d is Ti-Co / 20 Ca-750 From the SEM images, we can see that Mo-Co / 4 Ca-750 The morphology is three-dimensional flower-like. Mo-Co / 40 Mg-750 With Ti-Co / 20 Ca-750The typical layered accordion-like morphology of MXene is still maintained. This shows that the catalyst of the present invention uses MXene as a carrier, effectively disperses and anchors cobalt atoms with the help of CaCl2 or MgCl2, has a high degradation rate for organic pollutants, low cobalt leaching, and good stability.

[0067] Figure 2 The catalyst Mo-Co / 4 prepared in Example 2 Ca-750 , the catalyst Mo-Co / 40 prepared in Example 4 Mg-750 , the catalyst Ti-Co / 20 prepared in Comparative Example 3 Ca-750 XRD spectrum. From the XRD diagram, it can be seen that the phase of the catalyst prepared in Example 2 and Example 4 is Mo2C, and the phase of the catalyst prepared in Comparative Example 3 is Ti3C2. This shows that the present invention selects alkaline earth metal chlorides such as CaCl2 and MgCl2 as fluxes, and forms a mixed molten salt etchant with cobalt chloride, which can successfully etch MAX and obtain the corresponding MXene phase.

[0068] In summary, the present invention uses MAX as a raw material and CaCl2 or MgCl2 as a molten salt etchant. At a specific mixing ratio and temperature, the addition of CaCl2 or MgCl2 is conducive to the dispersion of Co, making Co more stably fixed on MXene, enhancing the activation of PMS while reducing the leaching of Co. In particular, for molybdenum-based MAX, a three-dimensional flower shape is formed after preparation, further significantly improving the catalytic performance of molybdenum-based catalysts.

Claims

1. A method for preparing a carbide-supported cobalt catalyst, characterized in that: The following steps are involved: (1) fully grinding the MAX phase; the MAX phase is one or two of Mo2TiAlC2 and Mo3AlC2; (2) adding a cobalt source and a chloride salt to the MAX phase fine powder ground in step (1), grinding the mixture thoroughly to obtain a mixed powder; wherein the dosage ratio of the MAX phase to the cobalt source and the chloride salt is 0.5:0.0125-0.25:0.25-1; the cobalt source is an inorganic cobalt salt CoCl2·6H2O; and the chloride salt is a mixture of one or more of CaCl2 and MgCl2·6H2O in any proportion; (3) The mixed powder in step (2) is transferred to a covered alumina crucible, placed in a tubular furnace, calcined at 550-800° C. for 4-6 h under nitrogen protection, and naturally cooled in the tubular furnace to obtain a calcined carbide-supported cobalt catalyst.

2. The method according to claim 1, characterized in that The MAX phase is Mo2TiAlC2.

3. The method according to claim 1, characterized in that The usage ratio of the MAX phase, the cobalt source and the chloride salt is 0.5:0.125:0.

5.

4. The method according to claim 1, characterized in that: In step (3), the calcination temperature is 750° C. and the calcination time is 6 h.

5. The method according to claim 1, characterized in that Also includes a cleaning step: (4) Pour the carbide-supported cobalt catalyst obtained by calcining step (3) into an appropriate amount of deionized water, disperse it evenly by ultrasonication, wash it by centrifugation several times, and dry it at 40-80° C. for 12-24 hours.

6. A carbide-supported cobalt catalyst prepared by the method for preparing a carbide-supported cobalt catalyst according to any one of claims 1 to 5, wherein the carbide-supported cobalt catalyst is in a flower shape or an accordion shape.

7. Use of the carbide-supported cobalt catalyst according to claim 6 in activating persulfate to degrade organic pollutants.

8. The use according to claim 7, characterized in that: The organic pollutant is a mixture of one or more of fluorouracil, metronidazole, sulfamethoxazole, perfluorooctanoic acid, and norfloxacin.

9. The use according to claim 7, characterized in that: The persulfate is one of peroxymonosulfate and peroxydisulfate or a mixture of the two.

10. The use according to claim 7, characterized in that: Based on the volume of the aqueous solution of organic pollutants, the mass of the catalyst ranges from 0.5 to 1 g / L.

Citation Information

Patent Citations

  • Two-dimension carbide loaded metal simple substance nano-powder, and preparation method and application thereof

    CN105854913A

  • FeCo / MXene compound, and preparation method and application thereof

    CN109701572A

  • MXene-based nano composite wave-absorbing material and preparation method thereof

    CN111629575A

  • Catalytic material taking MXene as carrier to load cobalt and preparation method of catalytic material

    CN116265098A

  • Preparation method and application of carbon-coated titanium nitride loaded nickel-based electrocatalyst

    CN118147697A

Cited By

  • MXene composite metal monatomic material as sulfur positive electrode catalyst and application of MXene composite metal monatomic material in all-solid-state lithium-sulfur battery

    CN121355262A